Red Blood Cell Distribution Width is an Independent Predictor of AKI and Mortality in Patients in the Coronary Care Unit - Yugang Hu; Huilan Liu; Shuai Fu; Jing Wan; Xiaoning Li (Karger Publishers, 2017)
Background/Aims: We investigated the hypothesis that RDW is an independent predictor of acute kidney injury (AKI) and mortality in patients in the coronary care unit (CCU). Methods: In this prospective, observational study, we screened 412 adults admitted to the CCU at Zhongnan Hospital of Wuhan University from January 1, 2014 to June 1, 2015. AKI was defined based on the KDIGO-AKI criteria. The survivors were followed up for up to 2 years after hospital discharge. The primary endpoint of the study was the incidence of AKI, while the secondary endpoints of the study were in-hospital mortality and 2-year mortality. Results: RDW was significantly correlated with the acute physiology and chronic health evaluation II (APACHEII) score, hemoglobin, mean corpuscular volume, inflammatory marker levels, nutrition and renal function at the time of CCU admission. The incidence of AKI was much higher in the high RDW group (RDW ≥14.0%) than in the low RDW group, a finding that was confirmed by multivariable logistic regression, which showed that RDW was independently associated with the incidence of AKI (odds ratio (OR), 1.059, 95% coincidence interval (95% CI), 1.024-1.095, P=0.001). A total of 61 patients died during their hospital stay, and baseline RDW was also an independent predictor of in-hospital mortality (hazard ratio (HR), 1.129, 95% CI 1.005-1.268, P=0.041). Patients with a high RDW exhibited significantly higher 2-year mortality than patients with a low RDW during a median follow-up period of 19.8 months (P<0.001), and RDW independently predicted the risk of 2-year mortality (HR, 1.189, 95% CI 1.045 to 1.354, P=0.009) in the multivariate Cox proportional hazard analysis after adjustments for other clinical and laboratory variables. Conclusion: RDW is an independent predictor of AKI and mortality in patients in the CCU.